Editing nineteenth-century fiction : papers given at the Thirteenth Annual Conference on Editorial Problems, University of Toronto, 4-5 November, 1977 /: papers given at the Thirteenth Annual Conference on Editorial Problems, University of Toronto, 4-5 November, 1977. (2016) - Unknown
No abstract available